TANTANGAN TERHADAP INTEGRASI: PENGARUH ISLAMOFOBIA TERHADAP POLITIK EROPA - Tambunan, Putri Marlen Noviana; Baiti, Ainun Nur (UIN Alauddin Makassar, 2025)
The purpose of this Journal is to find what are the challenges for Integration of Islamophobia's influence on politics in Europe, we know that Islam is the second largest religion in Europe, so its existence could have a significant influence on the political structure in Europe. This research uses descriptive qualitative research method, which makes literature research as its main reference, we use this method to analyze data from previous research. This research will focus on what are challenges to integration and European political order will be faced by people in Europe due to emergence of Islamophobia there. The main purpose of using Descriptive Qualitative method is so that the author can elaborate the issues to be discussed systematically in accordance with accurate and accountable facts. From this research, it’s found that the presence of Muslim immigrants in Europe has led to a rejection attitude from local community as they consider it’s presence as a threat to national identity, cultural values, and democratic principles that are upheld by European countries. One of the main reasons for this discrimination is that Islamic religious beliefs are not in line with concept of secularism, which is the basis of most countries in Europe.